Survei Deskriptif Self-Determined Motivation Pemain Sepak Bola PFA Sukoharjo - Wahyu Adi Utomo; Yudi Karisma Sari; Risa Agus Teguh Wibowo (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the self-determined motivation profile of football players at PFA Sukoharjo. Employing a descriptive quantitative approach with a cross-sectional design, this research involved 30 players. The subjects’ characteristics included an average age of 14±0.00 years, playing experience of 3.69±0.77 years, body weight of 50.40±10.51 kg, height of 160.51±11.10 cm, and a Body Mass Index (BMI) within the normal category (19.49±2.36). The sample was selected using a purposive sampling technique. Data were collected using the Sport Motivation Scale-II (SMS-II) and analyzed through descriptive statistical techniques. The results indicate that PFA Sukoharjo players dominantly possess very strong autonomous motivation. This is evidenced by high mean scores in the dimensions of intrinsic motivation (18.67), identified regulation (18.67), and integrated regulation (18.40). Conversely, controlled motivation dimensions showed significantly lower values, namely introjected regulation (11.17), external regulation (8.23), and amotivation (4.80). The low standard deviation (2.864) indicates a consistent motivation profile across the entire sample. Based on self-determination theory, the players exhibit an ideal motivational profile with a continuum pattern that declines sharply from autonomous regulation to amotivation. This pattern reflects a healthy psychological state, where football activities have become integrated into the players’ self-identity. These findings imply high mental resilience and potential for long-term involvement in football careers at PFA Sukoharjo.